A negative charge at position D+5 of Motif A is critical for function of the major facilitator superfamily multidrug/H+antiporter MdtM. (13th January 2022) - Meaney, Steve; Law, Christopher J.
Abstract: The phenomenon of antimicrobial resistance represents a major public health risk. The activity of integral membrane transporter proteins contributes to antimicrobial resistance in pathogenic bacteria and proton gradient-driven multidrug efflux representatives of the major facilitator superfamily (MFS) of secondary transporters are the dominant antimicrobial efflux proteins in Escherichia coli. In many, but not all, of the characterized MFS multidrug transporters, an aspartic acid residue at position D +5 of the conserved signature Motif A is essential for transport activity. The present work extends those studies to the E. coli MFS multidrug/H + antiporter MdtM and used a combination of mutagenesis, expression studies, antimicrobial resistance assays, and transport activity measurements to reveal that a negatively charged residue at position D +5 is critical for MdtM transport function.